Instructive roles and supportive relationships: client perspectives of their engagement with community health workers in a rural south African home visiting program - Christina A. Laurenzi; Sarah Skeen; Bronwynè J. Coetzee; Vuyolwethu Notholi; Sarah Gordon; Emma Chademana; Julia Bishop; Mark Tomlinson (BMC, 2021)
Abstract Background Community health worker (CHW) programs have been positioned as a way to meet the needs of those who experience marginalization and inequitable access to health care, and current global health narratives also emphasize their adaptable nature to meet growing health burdens in low-income settings. However, as CHW programs adopt more technical roles, the value of CHWs in building relationships with clients tends to be overlooked. More importantly, these programs are often reframed and redeployed without attending to the interests and needs of program clients themselves. We set out to gather perspectives of program and CHW engagement from clients of a maternal and child health program in rural South Africa. Methods We conducted 26 interviews with pregnant or recently-delivered clients of the Enable Mentor Mother program between February-March 2018. After obtaining informed consent, a trained research assistant conducted all interviews in the clients' home language, isiXhosa. Interviews, translated and transcribed into English, were organized and coded using ATLAS.ti software and thematically analyzed. Results We found that clients' home-based interactions with Mentor Mothers were generally positive, and that these engagements were characterized by two core themes, instructive roles and supportive relationships.. Instructive roles facilitated the transfer of knowledge and uptake of new information for behavior change. Relationships were developed within the home visit setting, but also extended beyond routine visits, especially when clients required further instrumental support. Clients further discussed a sense of agency gained through these interactions, even in cases where they chose not to, or were unable to, heed their Mentor Mother's advice. Conclusions These findings highlight the important roles that CHWs can assume in providing both instructive and supportive care to clients; as deepening relationships may be key for encouraging behavior change, these findings pinpoint the need to bolster training and support for CHWs in similar programs. They also emphasize the importance of integrating more channels for client feedback into existing programs, to ensure that clients' voices are heard and accounted for in shaping ongoing engagement within the communities in which these programs operate.